2015
DOI: 10.1016/j.jval.2015.09.2862
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with life of general population of pakistan. A nation wide survey

Abstract: A743reviewing how the use of a structured model for emotions can improve PRO instrument development by strengthening the role of emotions during CE. Methods: A literature review of CE with emotional motivations was undertaken to identify the most salient aspects for PRO instrument development. Results: The method for eliciting emotional motivations is based on motivation research and extraction techniques (see Forbes, 2010) containing, nine distinct categories of emotional motivation. The CE protocol relies up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Satisfaction with Life Scale has also been administered to a sample of Spanish adolescents in an elaborate study to determine longitudinal invariance which showed nonsignificant age, gender, and longitudinal variance ( 32 ). Additionally, researchers have used the SWLS on the Pakistani population and concluded that 30.5% of the population was satisfied with their lives ( 33 ). Similar findings were shown in another study ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Satisfaction with Life Scale has also been administered to a sample of Spanish adolescents in an elaborate study to determine longitudinal invariance which showed nonsignificant age, gender, and longitudinal variance ( 32 ). Additionally, researchers have used the SWLS on the Pakistani population and concluded that 30.5% of the population was satisfied with their lives ( 33 ). Similar findings were shown in another study ( 34 ).…”
Section: Discussionmentioning
confidence: 99%